2022
DOI: 10.1027/0227-5910/a000814
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Suicide Ideation in Lithuania and Poland Amid the COVID-19 Pandemic

Abstract: Abstract. Background: The COVID-19 pandemic had an impact on many risk and protective factors associated with suicide. Aims: The aim of this study was to identify pandemic-related factors associated with suicidal ideation in the two European countries, Lithuania and Poland, amid the COVID-19 pandemic. Method: The sample comprised 2,459 participants in both countries; 57.2% of the respondents were female. The M age of the participants was 43.45 years ( SD = 15.91). Pandemic-related stressors and adjustment prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…Such high estimates may be linked to general suicidality; it remains unclear, however, to what extent did the pandemic specifically affect students’ suicidal ideation and behavior. Previous research indicate pandemic-related stressors such as impaired family functioning, loneliness, and burden due to staying at home to be strongly related to suicidal ideation [ 95 , 96 ]. Our study, however, did not highlight any of the pandemic-associated variables to be significantly predictive for suicidal ideation, planning or attempt during the last year.…”
Section: Discussionmentioning
confidence: 99%
“…Such high estimates may be linked to general suicidality; it remains unclear, however, to what extent did the pandemic specifically affect students’ suicidal ideation and behavior. Previous research indicate pandemic-related stressors such as impaired family functioning, loneliness, and burden due to staying at home to be strongly related to suicidal ideation [ 95 , 96 ]. Our study, however, did not highlight any of the pandemic-associated variables to be significantly predictive for suicidal ideation, planning or attempt during the last year.…”
Section: Discussionmentioning
confidence: 99%
“…también se describe una disminución global de las tasas de suicidio durante el confinamiento, aunque con aumento en determinadas clases sociales 9 . Otros, sin embargo, sí que detectaron un aumento de las ideas de suicidio en relación con los problemas de adaptación, la soledad y la sobrecarga por tener que estar más tiempo en casa debido al confinamiento 10,11 .…”
Section: Introductionunclassified
“…In descriptions post-pandemic, it was reported that social isolation, anxiety, fear of contagion, uncertainty, chronic stress and economic difficulties can contribute to the development or exacerbation of stress-related illnesses and suicide 33 . In Poland and Lithuania, it was found that high levels of adjustment problems, loneliness and staying longer at home during the COVID-19 pandemic were significantly associated with suicidal ideation 34 .…”
Section: Variablesmentioning
confidence: 99%